1999
DOI: 10.1007/s005850050829
|View full text |Cite
|
Sign up to set email alerts
|

Observations of plasma density structures in association with the passage of traveling convection vortices and the occurrence of large plasma jets

Abstract: Abstract. We report important results of the ®rst campaign specially designed to observe the formation and the initial convection of polar cap patches. The principal instrumentation used in the experiments comprised the EISCAT, the Sondrestrom, and the Super DARN network of radars. The experiment was conducted on February 18, 1996 and was complemented with additional sensors such as the Greenland chain of magnetometers and the WIND and IMP-8 satellites. Two dierent types of events were seen on this day, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 20 publications
2
21
0
Order By: Relevance
“…Several investigations of TCV events were carried out using the Super Dual Auroral Radar Network (SuperDARN) measurements. Convection velocities of TCVs obtained by magnetometer networks and SuperDARN were found to be consistent (Lyatsky et al, 1999;Valladares et al, 1999;Kataoka et al, 2001). Kataoka et al (2001) also found that SuperDARN data show a pronounced increase in the backscatter power and the Doppler spectral width as the TCV passes through the irregularity region.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…Several investigations of TCV events were carried out using the Super Dual Auroral Radar Network (SuperDARN) measurements. Convection velocities of TCVs obtained by magnetometer networks and SuperDARN were found to be consistent (Lyatsky et al, 1999;Valladares et al, 1999;Kataoka et al, 2001). Kataoka et al (2001) also found that SuperDARN data show a pronounced increase in the backscatter power and the Doppler spectral width as the TCV passes through the irregularity region.…”
Section: Introductionsupporting
confidence: 52%
“…Also, Lühr et al (1993Lühr et al ( , 1996 indicated that the Hall conductivity decreased in the upward field-aligned current region of a TCV. Valladares et al (1999) showed that a section of the high-latitude plasma density was eroded by a factor of 2 during a TCV event, producing magnetic perturbations larger than 100 nT. Several investigations of TCV events were carried out using the Super Dual Auroral Radar Network (SuperDARN) measurements.…”
Section: Introductionmentioning
confidence: 99%
“…An association between patches and transient reconnection pulses has been suggested by a number of recent studies Lockwood et al, 2000Opgenoorth et al, 2001;Moen et al, 2001). Other studies suggest patches are linked to other phenomena, such as travelling convection vortices (Valladares et al, 1994(Valladares et al, , 1999.…”
Section: Polar Cap Patchesmentioning
confidence: 87%
“…[T e ] 2 ( K ) be enhanced (Whitteker, 1977;Walker et al, 1999;Millward et al, 1999;Vontrat-Reberac et al, 2001) and this is indeed observed in the cusp/cleft region (Titheridge, 1976;Curtis et al, 1982;Doe et al, 2001). However, as the field lines convect poleward of the cusp/cleft into the mantle and polar cap precipitation regions, modelling studies show T e will fall rapidly as the precipitation flux decays; on the other hand N e will decay only slowly (Watermann et al, 1994;Davis and Lockwood, 1996;).…”
Section: Patch Enhancement By Magnetosheath Precipitationmentioning
confidence: 99%
See 1 more Smart Citation